Pengolahan Sampah Rumah Tangga Menjadi Kompos di Kelurahan. Labuh Baru Timur Pekanbaru - Ambar Tri Ratna Ningsih; Latifa Siswati (Universitas Lancang Kuning, 2021)
Garbage Used newspapers and paper are garbage that is produced in many households and in office environments. Kedungsari Village has an environmental love group formed by the name of the Waste Bank Cadre. This group exists in every RW and consists of two people who are appointed as pioneers in managing waste in their environment to be used as a source of income for their citizens. So far the garbage collected is still limited to the crude form of the waste and is exchanged for the rupiah, but with the initial form of transformation into an aesthetic value form it will increase the selling value of the waste. The method of implementing this PKM activity includes: Extension, Demonstration, Training, Mentoring, and Evaluation. The results of the community service activities carried out in Kedungsari Subdistrict, Sukajadi District, Pekanbaru, increased the knowledge of participants in managing used papers or newspapers for 62.50%, and obstacles that could hinder the craft of managing paper or used newspapers. So that the Kelurahan apparatus must make a policy to form a local market that can provide motivation to artisans to use used paper or used newspapers to be a selling value item.